2021
DOI: 10.3389/fphys.2021.675289
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise Hypotension Following a Single Bout of High Intensity Interval Exercise vs. a Single Bout of Moderate Intensity Continuous Exercise in Adults With or Without Hypertension: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Background: Post-exercise hypotension (PEH) is an important tool in the daily management of patients with hypertension. Varying the exercise parameters is likely to change the blood pressure (BP) response following a bout of exercise. In recent years, high-intensity interval exercise (HIIE) has gained significant popularity in exercise-based prevention and rehabilitation of clinical populations. Yet, to date, it is not known whether a single session of HIIE maximizes PEH more than a bout of moderate-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Most studies of PEH have reported measurements only for the initial hour after exercise ( Marcal et al, 2021 ). Thus it is difficult to compare our subjects’ PEH responses over longer postexercise periods with published data.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of PEH have reported measurements only for the initial hour after exercise ( Marcal et al, 2021 ). Thus it is difficult to compare our subjects’ PEH responses over longer postexercise periods with published data.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies included in this metaanalysis used a combination of aerobic and resistance exercise in water or land; one used only aerobic exercise, and the last used High Intensive Interval Exercise (HIIE). A recent metaanalysis showed that land HIIE promoted a larger PEH than moderate-intensity continuous exercise on ambulatory daytime blood pressure (Marçal et al, 2021). Another meta-analysis showed that several types of regular AE as swimming, deep water, circuits, resistance, and others, significantly reduce the blood pressure in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our sample was normotensive and we assessed blood pressure a few minutes after exercise while a review of the literature on post-exercise hypotension found larger effects for hypertensive samples and the magnitude of the reduction in blood pressure was larger 2-h post-exercise compared to 1-h post-exercise ( Casonatto et al, 2016 ). Additionally, the lack of effects for blood pressure for a single short bout of stair walking are not necessarily indicative of the known improvements in hypertension for longer bout duration or sustained behavior change ( Marçal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%